Linking knowledge with action in the pursuit of sustainable water-resources management - Katharine Jacobs (2018)
Managing water for sustainable use and economic development is both a technical and a governance challenge in which knowledge production and sharing play a central role. This article evaluates and compares the role of participatory governance and scientific information in decision-making in four basins in Brazil, Mexico, Thailand, and the United States. Water management institutions in each of the basins have evolved during the last 10-20 years from a relatively centralized water-management structure at the state or national level to a decision structure that involves engaging water users within the basins and the development of participatory processes. This change is consistent with global trends in which states increasingly are expected to gain public acceptance for larger water projects and policy changes. In each case, expanded citizen engagement in identifying options and in decision-making processes has resulted in more complexity but also has expanded the culture of integrated learning. International funding for water infrastructure has been linked to requirements for participatory management processes, but, ironically, this study finds that participatory processes appear to work better in the context of decisions that are short-term and easily adjusted, such as water-allocation decisions, and do not work so well for longer-term, high-stakes decisions regarding infrastructure. A second important observation is that the costs of capacity building to allow meaningful stakeholder engagement in water-management decision processes are not widely recognized. Failure to appreciate the associated costs and complexities may contribute to the lack of successful engagement of citizens in decisions regarding infrastructure.